Quantum disordered phase on the frustrated honeycomb lattice - Cabra, Daniel Carlos (2011)
In the present paper we study the phase diagram of the Heisenberg model on the honeycomb lattice with antiferromagnetic interactions up to third neighbors along the line J₂=J₃ that includes the point J₂=J₃=J₁/2, corresponding to the highly frustrated point where the classical ground state has macroscopic degeneracy. Using the linear spin-wave theory and the Schwinger boson technique followed by a mean field decoupling and exact diagonalization for small systems, we find an intermediate phase with a spin gap and short-range Néel correlations in the strong quantum limit S=½. All techniques provide consistent results which allow us to predict the existence of a quantum disordered phase, which may have been observed in recent high-field ESR measurements in manganites.